The Impact of Youth Unemployment on Crime and Migration in Turkiye: An Empirical Assessment - Umar, Tuba (Fırat Üniversitesi, 2025)
Unemployment is one of the leading economic problems today. The youth, who constitute the majority of the population, are more severely affected by unemployment compared to other segments of society, and this leads to serious long-term issues. In Turkiye, youth unemployment stands out as a significant socio-economic problem that deeply affects not only individuals but also society as a whole. The rise in unemployment rates contributes to impoverishment, a decline in living standards, and social exclusion, ultimately leading to the deterioration of interpersonal relationships. A review of the literature reveals that many studies on unemployment have focused primarily on theoretical aspects. Unlike previous studies, this research provides an empirical contribution to the literature by analyzing the impact of youth unemployment on crime and migration. Using data from the period 2008–2020, the relationship between youth unemployment, crime, and migration in Turkiye's NUTS-1 (Level 1) regions is examined through a panel data analysis method. The primary aim of this study is to analyze the effects of youth unemployment on crime and migration within Turkiye. According to the findings of the Driscoll and Kraay robust estimator, migration has a statistically significant and negative effect on youth unemployment at the 1% significance level across 12 regions of Turkiye. However, it was found that crime has an insignificant effect on youth unemployment.

Günümüzde işsizlik ekonomik sorunların başında gelmektedir. Nüfusun büyük çoğunluğunu oluşturan genç kesim işsizlik probleminden diğer kesime göre daha fazla etkilenip, uzun vadede ciddi sorunlarla karşılaşmaktadırlar. Türkiye’de genç işsizlik, sadece bireyleri değil, toplumu da derinden etkileyen önemli bir sosyo-ekonomik sorun olarak karşımıza çıkmaktadır. İşsizlik oranlarındaki artış kişinin yoksullaşmasına, yaşam standardının düşmesine ve toplumdan dışlanarak insan ilişkilerinin bozulmasına neden olmaktadır. Literatürde, işsizlik üzerine yapılan çalışmaların birçoğunun teorik olarak ele alındığı görülmektedir. Bu çalışmada ise diğer çalışmalardan farklı olarak genç işsizliğin işlenen suçlar ve göç hareketleri üzerindeki etkisi ampirik olarak analiz edilerek literatüre özgün bir katkı sağlanmıştır. Çalışmada, 2008-2020 dönemi verileri kullanılarak Türkiye’nin İstatistiki Bölge Birimleri Sınıflamasına (İBBS) çerçevesindeki Düzey 1 bölgelerinde genç işsizlik, suç ve göç arasındaki ilişki panel veri analiz yöntemiyle incelenmiştir. Bu araştırma, Türkiye’de genç işsizlik sorununun suç ve göç üzerindeki etkilerini analizler çerçevesinde incelemeyi amaçlamaktadır. Panel, Driscoll ve Kraay dirençli tahmincinin bulgularına göre, Türkiye’nin 12 bölgesinde, %1 önem düzeyinde göçün genç işsizlik oranları üzerinde negatif yönde ve anlamlı etkilerinin olduğu bulunmuştur. Ancak işlenen suçların genç işsizlik oranları üzerinde anlamsız etkisinin olduğu tespit edilmiştir.
TÜRKİYE’DE GENÇ İŞSİZLİĞİN SUÇ VE GÖÇ ÜZERİNDEKİ ETKİLERİ: AMPİRİK BİR DEĞERLENDİRME
Keywords: Macroeconomics (Other); Makro İktisat (Diğer); Microeconomics (Other); Mikro İktisat (Diğer)